2015
DOI: 10.15407/cryo25.04.311
|View full text |Cite
|
Sign up to set email alerts
|

Physical and mechanical properties of devitalized xenografts based on pericardium, aortic valve leaflets and arteries

Abstract: Реферат: Изучали физико-механические свойства ткани перикарда, створок аортального клапана и артерий свиньи на этапах девитализации криорадиационным способом. Для предымплантационной обработки ксенотканей использовали низкие температуры и ионизирующее излучение. Проводили тест одноосного растяжения тканей после замораживанияотогрева, облучения потоком электронов, а также после их сочетанного воздействия. Показано, что экстрацеллюлярный матрикс (ЭЦМ) девитализированных тканей сохраняет свою целостность и облада… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Thus, after subsequent treatments with low temperature and irradiation, the physical and chemical changes within the pericardium tissue resulted in a cascade of structural rearrangements, which led to the formation of additional cross links and more stable connective-tissue structure, preventing early enzymatic graft biodegradation within the recipient organism. These findings allow us to conclude that the modified tissue with the given characteristics could persist for a long time within the conditions of the body (which enabled repopulation and new structural formation processes), endure work load during functioning, while preserving tensile property and resistance to fracture and twisting (12, 17).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Thus, after subsequent treatments with low temperature and irradiation, the physical and chemical changes within the pericardium tissue resulted in a cascade of structural rearrangements, which led to the formation of additional cross links and more stable connective-tissue structure, preventing early enzymatic graft biodegradation within the recipient organism. These findings allow us to conclude that the modified tissue with the given characteristics could persist for a long time within the conditions of the body (which enabled repopulation and new structural formation processes), endure work load during functioning, while preserving tensile property and resistance to fracture and twisting (12, 17).…”
Section: Discussionmentioning
confidence: 83%
“…Deep freezing and β-radiation initiated the formation of additional interlinking and cross-linking; a synergistic effect was exhibited, producing significantly enforced tissue strength and elastic properties. Thus a more compact arrangement and strengthening fibers ensured structural stabilization and graft conservation: the xenografts retained safety margin, skeleton, elasticity, extensibility, resistance to fracture and twisting (10, 12).…”
Section: Introductionmentioning
confidence: 99%
“…Almost all data on mechanical properties in longitudinal tension remained at the level of control values of the corresponding subgroups (decellularized and non-decellularized). Such anisotropy of biomechanical properties in the connective tissue scaffold of the aortic wall is explained by the peculiarities of the three-dimensional orientation of CTF fibers, which provides effective compensation of intravascular fluid pressure pulsation to maintain active blood flow [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The deformability of the material is reflected in the relative elongation under tension indicator. This indicator is influenced by the structure and fiber composition of the tissue [ 43 ]. Previously, it was shown that the main mass of elastin fibers in the aortic wall is located in the media as part of elastin lamellae, which are predominantly arranged in the circumferential direction [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%